1996
DOI: 10.1089/hum.1996.7.16-1937
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer into Hepatocytes and Human Liver Tissue by Baculovirus Vectors

Abstract: Gene therapy of liver diseases requires the development of efficient vectors for gene transfer in vivo. Retroviral and adenoviral vectors have been shown to deliver genes efficiently into hepatocytes in vitro and in vivo. However, these vectors do not allow for exclusive infection of the liver which would be highly advantageous for in vivo gene therapy strategies. We have recently demonstrated that genetically modified baculoviruses (Autographa californica nuclear polyhedrosis virus) efficiently deliver genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
113
1
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 44 publications
0
113
1
1
Order By: Relevance
“…11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes. 6,11,12 In these studies, baculovirus-mediated gene delivery was highly efficient (470%) and homogeneous. However, these studies were carried out using cells in short-term culture conditions and as such, the hepatocytes were poorly differentiated and do not have intact paracellular junctions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes. 6,11,12 In these studies, baculovirus-mediated gene delivery was highly efficient (470%) and homogeneous. However, these studies were carried out using cells in short-term culture conditions and as such, the hepatocytes were poorly differentiated and do not have intact paracellular junctions.…”
Section: Discussionmentioning
confidence: 97%
“…56 Complement inactivation of baculoviruses can be overcome by the depletion of viral neutralizing factors in the sera prior to baculovirus infection. 12,56,57 The effects of the complement system have also been overcome by the generation of complement-resistant baculoviruses. 58 In order to test the efficacy of baculovirus vectors prior to in vivo gene therapy, an in vitro system of baculovirusmediated gene transfer with similar hepatocyte biology to the in vivo liver must be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that gp64-pseudotyped lentiviral vectors efficiently transfer the human Factor IX gene or the GFP gene to mouse cells following portal vein injection, contrary to several published studies that baculovirus vectors are not infectious if injected into the vasculature of mice. 18,32 This indicates that the baculovirus infection is blocked at the postentry step and not at the receptor-binding or entry stage. The selectivity of the Ampho-pseudotyped lentiviral vectors for transduction of hepatocytes was interesting and novel.…”
Section: Discussionmentioning
confidence: 99%
“…16 Early studies showed that baculovirus vectors could efficiently transduce human hepatocyte cell lines and explanted human liver tissue. 17,18 Subsequently, it was demonstrated that baculovirus vectors could enter a broader variety of human cell types. [19][20][21] We set out to determine whether gp64 could be used to pseudotype other viral vectors and confer high infectivity in cells of hepatic origin, which are primary targets for many genetherapy applications.…”
Section: Introductionmentioning
confidence: 99%